A novel biocompatible Eu-based coordination polymers of cytarabine anticancer drug: Preparation, luminescence properties and in vitro anticancer activity studies - Zeng, Zhijun; Shen, Huaxiang; Gao, Wei; Guo, Qifeng; Chen, Mengjie; Yan, Xiaojun; Liu, Hongning; Ji, Yanhua (Frontiers in Chemistry, 2022)
In this study, we use cytarabine anticancer drug to synthesize a new rare earth complex with Europium ion. The study work is an attempt to investigate luminescence and biological properties of the Eu-based coordination polymers of cytarabine (Eu-CP-Ara) anticancer drug which have been prepared by us. Eu-CP-Ara has luminescence properties with emission centering at about 619 nm excited with 394 nm. We study cytarabine and Eu-CP-Ara in vitro cytotoxicity. Cytotoxicity of Eu-CP-Ara against lung cancer cells (A549) could even be comparable to the inhibitory effect of cytarabine ligands, showing the advantage of antitumor activity. In addition, EU-CP-Ara showed lower cytotoxicity to normal liver cells (L02). At the same, from the CLSM images, Eu-CP-Ara has successfully entered the A549 cell. Hence, Eu-CP-Ara can be used as a potential anticancer drug. Eu-CP-Ara may be an effective strategy for the tracking cytarabine against tumours and might impart better accurate treatment effect and therapeutic efficiency.